Inhibitory effect of digoxin on testosterone secretion through mechanisms involving decreases of cyclic AMP production and cytochrome P450(scc) activity in rat testicular interstitial cells - Lin, Ho (1998)
1. In vivo and in vitro experiments were performed to examine inhibitory effects of digoxin on testosterone secretion and to determine possible underlying mechanisms. 2. A single intravenous injection of digoxin (1 μg kg(−1)) decreased the basal and human chorionic gonadotropin (hCG)-stimulated plasma testosterone concentrations in adult male rats. 3. Digoxin (10(−7)–10(−4) M) decreased the basal and hCG-stimulated release of testosterone from rat testicular interstitial cells in vitro. 4. Digoxin (10(−7)–10(−4) M) also diminished the basal and hCG-stimulated production of cyclic 3′ : 5′-adenosine monophosphate (AMP) and attenuated the stimulatory effects of forskolin and 8-Br-cyclic AMP on testosterone production by rat testicular interstitial cells. 5. Digoxin (10(−4) M) inhibited cytochrome P450 side chain cleavage enzyme (cytochrome P450(scc)) activity (conversion of 25-hydroxy cholesterol to pregnenolone) in the testicular interstitial cells but did not influence the activity of other steroidogenic enzymes. 6. These results suggest that digoxin inhibits the production of testosterone in rat testicular interstitial cells, at least in part, via attenuation of the activities of adenylyl cyclase and cytochrome P450(scc).